Correlation Between GGMPlus, Topex and BGI Gravity Data in Volcanic Areas of Java Island. Issue 1 (February 2021) - Suprianto, Agus; Supriyadi,; Priyantari, Nurul; Eko Cahyono, Bowo
Abstract: There are several secondary gravity data on the internet that can be freely accessed and downloaded for research purposes. These gravity data include Topex Gravity data, which provides free-air gravity data, BGI (Observation Gravity data, Free-Air, Complete Anomaly Bouguer), and GGMPlus Gravity Data. GGMPlus gravity data is gravity data with the smallest grid spacing compared to Topex and BGI data, with a grid spacing of approximately 200 meters. This data consists of 5 data sets, including Gravity Disturbance and Gravity Acceleration data. This study correlates between Topex and BGI free-air data with GGMPlus data (Gravity Disturbance and Gravity Acceleration), and BGI Observation Gravity data with GGMPlus (Gravity Disturbance and Gravity Acceleration) data using Pearson correlation technique. Correlated data are gravity data in volcanic regions in Central and East Java. As a result, Gravity Disturbance data on GGMPlus is equivalent to Free-Air Gravity Data on Topex and BGI, while Gravity Accelerations Data is equivalent to BGI Observation Gravity data, with a correlation level above 95%.